HUBUNGAN MANUSIA DAN ALAM DALAM QASĪDAT SYAJARAT AZ-ZAYTŪN ATH-THĀNĪYAH KARYA MAHMOUD DARWISH (KAJIAN EKOKRITIK SASTRA LAWRENCE BUELL) - Putri, Amelia Febriana; Nida, Nushrotun; Nugraha, Rahmat Mulya; Nurhidayat, Ari; Pamungkas, Rumi; Al Haqiqi, Muhammad Jundullah (LPPM STAI Al-Azhary Cianjur, 2025)
This study aims to analyze the relationship between humans and nature in the poem